Outcome from out-of-hospital cardiac arrest managed by the pre-hospital emergency medical system in Martinique, a French Caribbean Overseas Territory - Florian Negrello; Jonathan Florentin; Romain Jouffroy; Vianney Aquilina; Rishika Banydeen; Rémi Neviere; Dabor Resiere; Moustapha Drame; Papa Gueye (Resuscitation Plus)
Introduction: Out-of-hospital cardiac arrest (OHCA) affects approximately 46,000 people in France annually and survival remains low. There is no published data specific to the characteristics and outcomes of OHCA in French overseas territories, especially in the French Caribbean territories. The aim of this study was to describe the characteristics and outcomes of adult OHCA patients managed by the Emergency Medical Service team (EMS) in Martinique. Methods: All adults with OHCA, managed by the EMS of Martinique between January 1st 2018 and June 30th 2019, were included. Primary outcome was 30 day-survival and neurological outcome at 30 days assessed by the Cerebral Performance Category scale (CPC). Secondary outcomes were return of spontaneous circulation (ROSC) prior to hospital admission and causes of cardiac arrest in patients with ROSC. Results: This study included 340 OHCA patients. The population was predominantly male (64%), with a median age of 68 [54–78] years. OHCA resulted from a medical condition in 314 patients (92%) and occurred mainly at home (75%), in the presence of witnesses for 235 patients (69%). Basic life support was initiated in 174 OHCA (51%). Median time to first-responders’ and prehospital mobile intensive care unit’s arrivals at scene were 17 [10–30] and 27 [19–41] minutes after call to the EMS dispatching center for OHCA. Non-shockable initial rhythm was present in 315 patients (93%), and 240 patients (71%) received advanced life support. Thirty-one patients (9%) achieved ROSC. On day 30, 13 patients (3.8%) were still alive, and 8 of them (2.4%) were alive with a CPC score of 1 or 2. Conclusion: The overall adult OHCA survival rate and survival with good neurological status on day-30 in the French Caribbean island of Martinique are low. OHCA survival rate may be improved by educating the population on basic life support techniques and reducing the time responses for first-responders and prehospital mobile intensive care unit to reach patients.